2022
DOI: 10.1002/admi.202200047
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophobic Ag‐Decorated CuO Nanowire Arrays with Analyte‐Concentrating and Self‐Cleaning Binary Functions for Ultrasensitive and Recyclable Surface‐Enhanced Raman Scattering

Abstract: Surface‐enhanced Raman scattering (SERS) is considered a promising analytical technique for the detection of analytes. Considering the practical SERS detection, it is necessary to develop low‐cost, highly sensitive, and recyclable SERS‐active substrates. Here, a simple and flexible approach is proposed to fabricate a superhydrophobic Ag‐decorated CuO (named as CuO@Ag) nanowire array substrate with analyte‐concentrating and self‐cleaning binary functions for ultrasensitive and recyclable SERS detection. During … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Liu and co-authors reported a Au-coated TiO 2 nanotube array and confirmed its high SERS activity and photocatalytic degradation for rhodamine 6G (R6G) . Deng et al fabricated a Ag-decorated CuO nanowire array substrate with analyte-concentrating and self-cleaning functions for sensitive SERS detection . Macias–Montero et al constructed Ag@ZnO-supported nanorods with application in the SERS detection of R6G .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Liu and co-authors reported a Au-coated TiO 2 nanotube array and confirmed its high SERS activity and photocatalytic degradation for rhodamine 6G (R6G) . Deng et al fabricated a Ag-decorated CuO nanowire array substrate with analyte-concentrating and self-cleaning functions for sensitive SERS detection . Macias–Montero et al constructed Ag@ZnO-supported nanorods with application in the SERS detection of R6G .…”
Section: Introductionmentioning
confidence: 98%
“…20 Deng et al fabricated a Ag-decorated CuO nanowire array substrate with analyteconcentrating and self-cleaning functions for sensitive SERS detection. 21 Macias−Montero et al constructed Ag@ZnOsupported nanorods with application in the SERS detection of R6G. 22 However, these hybrid materials as SERS substrates have a series of problems, such as complicated preparation, limited sensitivity, and acid-intolerant properties.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Superhydrophobic Ag‐decorated CuO nanowire arrays were developed to enable ultrasensitive detection of Malachite Green molecules down to the sub‐picomolar level. [ 10 ] Nanostructured‐Au microisland arrays with wettability difference also demonstrated the ultrasensitive detection of femtomol Rhodamine 6G. [ 11 ] Nevertheless, the important feature of chip‐to‐chip reproducibility has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Nevertheless, the important feature of chipto-chip reproducibility has not been investigated. [10,11] Therefore, sensitive and reproducible SERS substrates using large-scale manufacturing processes are strongly desired for quantitative sensing in real applications. Recently, efficient and broadband plasmonic absorbers, composed of self-assembled metal NPs on the nanoporous templates, have received extensive research efforts because they support strong plasmonic resonances in a broad spectral band and can easily be fabricated over large areas with no need of lithography process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation